2009
DOI: 10.1158/1078-0432.ccr-08-1080
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Phase II Study of Lapatinib in Patients with Brain Metastases from HER2-Positive Breast Cancer

Abstract: Purpose: Brain metastases develop in one third of patients with advanced HER2+ breast cancer.Effective therapy for patients with central nervous system (CNS) progression after cranial radiation is extremely limited and represents a major clinical challenge. Lapatinib, an epidermal growth factor receptor/HER2 inhibitor, was associated with regressions of CNS lesions in a small phase 2 trial. The current study was done to further evaluate the CNS activity of lapatinib. The study was later amended to allow patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
373
1
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(400 citation statements)
references
References 18 publications
11
373
1
12
Order By: Relevance
“…More recently, there have been further reports of responses to lapatinib-based therapy. After an initial singlecentre phase II study of lapatinib monotherapy in patients with HER2-positive breast cancer who developed progressive CNS metastases after prior loco-regional therapy (Lin et al, 2008), a larger multicentre phase II study involving 242 patients reported a 6% CNS ORR to lapatinib alone (Lin et al, 2009). In an exploratory analysis, a further 21% patients experienced a X20% volumetric reduction in CNS lesions, with many having significant improvement in neurological symptoms.…”
Section: Pre-treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, there have been further reports of responses to lapatinib-based therapy. After an initial singlecentre phase II study of lapatinib monotherapy in patients with HER2-positive breast cancer who developed progressive CNS metastases after prior loco-regional therapy (Lin et al, 2008), a larger multicentre phase II study involving 242 patients reported a 6% CNS ORR to lapatinib alone (Lin et al, 2009). In an exploratory analysis, a further 21% patients experienced a X20% volumetric reduction in CNS lesions, with many having significant improvement in neurological symptoms.…”
Section: Pre-treatmentmentioning
confidence: 99%
“…A phase II study with single agent lapatinib 750 mg bid was undertaken in patients with HER2-positive CNS metastases who had shown progression in their brain after earlier whole-brain radiotherapy (WBRT), and clinical and radiological responses were observed (Lin et al, 2008). Subsequently, a larger multicentre phase 2 study involving 242 patients recently reported a 6% CNS objective response rate to lapatinib alone (defined as X50% volumetric reduction of CNS lesion(s) (Lin et al, 2009). In addition, a further 21% patients experienced a X20% volumetric reduction in their CNS lesions, of whom many had significant improvement in neurological symptoms.…”
mentioning
confidence: 99%
“…In an exploratory analysis, 21% of patients achieved at least a 20% reduction in the volume of their CNS lesions. Additional responses were documented in patients who joined an optional extension phase of the study and who were treated with lapatinib plus capecitabine after progression on lapatinib alone [43]. On the basis of the results of this study, prospective studies of lapatinib in combination with other chemotherapeutic agents, novel targeted agents and cranial radiotherapy are ongoing.…”
Section: Lapatinib In Brain Metastases From Breast Cancermentioning
confidence: 99%
“…При оценке частоты ответа метастазов в ГМ у ранее леченных больных лапатиниб в монотерапии показал эффективность в пределах от 2,6 до 6,0 % [31,32]. При добавлении капецитабина частота ответа воз-растала до 20-33 % [33][34][35][36].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified